Pilot study to evaluate the potential use of the renal resistive index as a preliminary diagnostic tool for chronic kidney disease in cats. Issue 10 (October 2018) - Matos, Ines; Azevedo, Pedro; Carreira, L Miguel
Objectives: Chronic kidney disease (CKD) is the most common renal pathology diagnosed in geriatric cats, and its prevalence increases with age. The arterial resistive index (RI) is important when evaluating vascular resistance and compliance, and can be applied in the kidney (renal RI [RRI]), allowing the evaluation of its vascular haemodynamics. The present study aimed to: (1) investigate in cats with CKD the relationships between the RRI and the following parameters: age, sex, body weight, plasmatic creatinine, blood urea nitrogen, potassium, urine specific gravity, urine protein:creatinine ratio and systolic arterial pressure; and (2) evaluate the potential use of the RRI as a preliminary diagnostic tool in cats with CKD. Methods: The present study involved 24 cats of both sexes. Six were healthy cats (control group [CG]) and 18 had CKD, but did not have any concomitant diseases and were not being treated with any medications (study group [SG]). For RRI measurement we used colour Doppler ultrasound (CDUS). Results: RRI differed significantly between the CG and SG ( P <0.01) and was higher in the SG. A statistically significant correlation was only achieved between the RRI and the body weight of the patients and it was negative. A strong and positive correlation was noted between the mean RRI of both kidneys (r = 0.66). Receiver–operating curve analysis allowed us to establish an admissible cut-off for the RRI value of 0.639 for a preliminary diagnosis of CKD for both kidneys. Conclusions and relevance: No differences were found for the RRI between the left and right kidneys, suggesting that evaluation of only one kidney is sufficient to provide an estimate of the RRI value for both organs. RRI measurement, which can be achieved with CDUS, is an easy-to-use diagnostic tool that, with a cut-off value of 0.639 for both kidneys, is useful in establishing a preliminary diagnosis of CKD.